Galectin 1 rescues microvascular alterations in Alzheimer’s disease in in vivo and in vitro models involving endoplasmic reticulum stress pathways - Presa, Jessica Lorena (2023)
As a multifactorial pathology, Alzheimer´s disease (AD) exhibits marked vascular alterations that correlate with disease progression. The immense impact of AD on individuals and healthcare systems calls for new therapeutics that would benefit from preventing vascular changes.